The influence of thermal treatments on the antioxidant activity and colour of chokeberry (aronia menocarpa) extract - Elena Criste (International Journal of Food Studies)
Natural ingredients are an important trend in the present day food industry since manufacturers are demanding natural food dyes originating from concentrates of plant origin. However, if the use of plant extracts as technological additives is intended, their stability should be evaluated. This paper presents research on the stability of a 50% ethanolic extract of chokeberry (Aronia melanocarpa) from the Republic of Moldova. The extract was subjected to various thermal regimes, i.e. -2 °C for 12 hours; 4 °C for 12 hours; 40 °C for 15 minutes, 60 °C for 15 minutes, 80 °C for 15 minutes and 100 °C for 2 minutes, after which the antioxidant activity and the colour parameters (CIELab) were evaluated. Three sets of extracts were also stored for 2 weeks at -2 °C; 4 °C; and 25-30 °C and afterwards the parameters mentioned above were measured once again. Furthermore, total content of polyphenols was determined using the Folin-Ciocalteu method. The antioxidant activity was stable at temperatures under 0 °C and temperatures as high as 100°C, as well as during storage at -2 °C, 4 °C and 25-30 °C. High temperatures however decreased the value of luminosity, and increased the redness, the yellowness and the chroma value which reached a maximum value of 55.66 after the extract was subjected to 100 °C for 2 minutes. Storage at room temperature significantly affected the luminosity of the extract by increasing its value from 42.36 to 50.22. For most treatments, the colour was stable and was not significantly modified.